Combined Chronotherapy for Poor Sleep Following Acute Coronary Syndrome: A Pilot Randomized Trial - Miguel Mendieta; Robin Cumella; Nakesha Fray; David Lopez-Veneros; David Hiti; Christina Franqui; Consuelo D’Agostino; Ian M. Kronish; Ari Shechter (Journal of Circadian Rhythms)
Sleep disturbance is common following acute coronary syndrome (ACS) and may contribute to a worse prognosis. We describe the rationale, design, and findings of a pilot and feasibility randomized clinical trial (RCT) of an intervention to improve post-ACS sleep. Fifteen post-ACS patients with insomnia and/or short sleep were randomized (2:1 allocation) to combined chronotherapy (CC) plus sleep hygiene education (SHE) or SHE control. CC was bright light therapy (BLT) delivered by a wearable light visor for 30 minutes after awakening and short-wavelength light avoidance using blue-light blocking (BLB) glasses in the evening from 8:00pm to bedtime daily for 4 weeks. Primary outcomes were feasibility, acceptability, appropriateness, usability, and adherence. Secondary outcomes were insomnia symptoms, sleep quality, and sleep duration. Two patients in the CC intervention group dropped before initiating study procedures. Completion of study procedures in remaining patients was high in the CC and control groups (88% and 100%, respectively). Self-reported adherence to CC (i.e., using BLT and BLB on ≥50% of days) was high (88% and 100%, respectively). The proportion of CC patients who perceived the intervention as feasible (71%) and usable (100%) was high, though fewer CC patients rated the intervention as acceptable (57%) and appropriate to improve sleep (29%). Improvements in insomnia symptoms and self-reported sleep quality and duration were seen in response to the CC intervention (71%). Post-ACS patients with sleep disturbance had high adherence to this chronotherapeutic intervention, and most viewed it as feasible and usable. This intervention should be tested in a larger RCT to determine efficacy to improve sleep. Trial Registration: ClinicalTrials.gov number NCT05299723 Date of registration: March 29, 2022 URL of trial registry record: https://classic.clinicaltrials.gov/ct2/show/NCT05299723